Pengembangan rencana induk ruang terbuka hijau berbasis masyarakat Desa Lambang Sari I, II, III Kecamatan Lirik Kabupaten Indragiri Hulu Riau - Sri Wulandari; Suwondo Suwondo; Gun Faisal (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The utilization of green open space (RTH) in Desa Lambang Sari I, II, III, Kecamatan Lirik Kabupaten Indragiri Hulu used for ordinary services, such as gardening, exercising, and interacting, aims to determine its utilization based on activity types, the actor, vegetation types, utilization time, and its contributions on socio-cultural, economic, and environmental aspects, as well as to build collaboration between the community and the government to create an integrated RTH. The methods applied to achieve these goals included (a) Identifying the existing conditions of public RTH to determine its form, type, and function, (b) identifying the RTH utilization patterns including its types, implementation time, actors and forms of management, frequency of utilization, benefits of activity implementation and, (c) identifying the role of the community in the public RTH utilization, and (d) formulating the development of RTH needed by Desa Lambang Sari I, II, III. In the end, a development master plan was created based on the needs of the community, which became the reference for the development of this green open space.